Spin excitations in layered cuprates: a Fermi-liquid approach - Eremin, I.; Manske, D. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
We review some important aspects of the doping dependence of many physical properties of the high-Tc cuprates based on a Fermi liquid-like approach. In particular, we show that the spin fluctuation-mechanism of superconductivity on the basis of a microscopic Eliashberg approach supports the idea that the symmetry of the superconducting order parameter is of dx2-y2 -wave type. Furthermore, the renormalization of the quasiparticle spectrum caused by the scattering on spin fluctuations results in the so-called kink feature seen in ARPES. The peculiar momentum dependence of the spin fluctuations will result in a strong anisotropy of the renormalization at different parts of the first Brillouin zone and thus will lead to a strong anisotropy of the kink. Another important achievement of the microscopic Eliashberg approach is that the spin excitations spectrum renormalizes strongly below Tc due to occurrence of superconductivity with a dx2-y2 -wave order parameter which yields to a formation of the so-called resonance peak that can be viewed as a spin exciton. The topology of the Fermi surface and the momentum dependence of the superconducting gap explains the peculiar dispersion of the resonance peak in good agreement with experiments.